Owner and veterinary surgeon perspectives on the roles of veterinary nurses and receptionists in relation to small animal preventative healthcare consultations in the United Kingdom - Belshaw, Zoe; Robinson, Natalie J.; Dean, Rachel S.; Brennan, Marnie L. (BMJ Publishing Group, 2018)
Veterinary receptionists and veterinary nurses rarely feature in published practice-based research, yet are integral to small animal veterinary practice in the United Kingdom (UK). The aim of this study was to investigate the perspectives of UK-based owners and veterinary surgeons about veterinary nurses and receptionists in relation to their role in preventative healthcare. Semi-structured telephone interviews were conducted with 15 dog and cat owners and 14 veterinary surgeons. Interview transcripts were thematically analysed. Reception staff were identified as having a range of important roles, from rapport building to providing healthcare information and advice. The perceived importance of those roles appeared to differ between owners and veterinary surgeons. Veterinary nurses were described as performing a diversity of roles in relation to preventative healthcare, both in the reception area and in the consulting room. Many owners, and some veterinary surgeons, expressed uncertainty about the remit and status of veterinary nurses in relation to providing veterinary advice. This study identifies for the first time the degree of responsibility for preventative healthcare given to veterinary receptionists and veterinary nurses in UK small animal practices. Further work is needed involving reception and nursing staff to fully appreciate and define their roles in small animal practice.